2020
DOI: 10.3389/fpsyg.2020.567784
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Severity of COVID-19 and Post-pandemic Consumption Willingness: The Roles of Boredom and Sensation-Seeking

Abstract: The COVID-19 pandemic restricts people's activities and makes consumer businesses suffered. This study explored the relationship between the perceived severity of COVID-19 and the post-pandemic consumption willingness. Study 1 surveyed 1464 Chinese people in March 2020, found the perceived severity of COVID-19 during the pandemic significantly increased the willingness to consume post-pandemic, and boredom stemming from limited activities and sensation-seeking expressions mediated this effect. Study 2 conducte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 53 publications
(72 reference statements)
1
52
1
1
Order By: Relevance
“…Although such prevention and control measures can effectively stop the spread of a pandemic (Remuzzi & Remuzzi, 2020), they also spawn a series of social governance issues and have negative impacts on general public's mental health (Ahmad & Murad, 2020;Horton, 2020;Wang et al, 2020c). A systematic review has proved that the COVID-19 is truly associated with psychology distress worldwide, such as anxiety and stress (Xiong et al, 2020), which may cause impulsive buying (Deng, Wang, Xie, Chao, & Zhu, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such prevention and control measures can effectively stop the spread of a pandemic (Remuzzi & Remuzzi, 2020), they also spawn a series of social governance issues and have negative impacts on general public's mental health (Ahmad & Murad, 2020;Horton, 2020;Wang et al, 2020c). A systematic review has proved that the COVID-19 is truly associated with psychology distress worldwide, such as anxiety and stress (Xiong et al, 2020), which may cause impulsive buying (Deng, Wang, Xie, Chao, & Zhu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to further investigate the phenomenon of impulsive buying in emergency and crisis situations. However, there is a limited number of studies on this issue (Thomas & Monica, 2002;Chow & Elkind, 2005;Deng et al, 2020), which mainly adopted a qualitative approach and lack empirical evidence. In addition, no empirical research has discussed the internal mechanism of impulsive buying in emergency and crisis situations.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the perceived threat of the pandemic attracted a great deal of attention from researchers in China and other countries of the world. At present, studies on threat perception of COVID-19 are mainly focused on its concern with economic confidence (Xin, 2020), anxiety reaction (Wen et al, 2020), pandemic-control confidence (Dryhurst et al, 2020), variety-seeking (Kim, 2020), and postpandemic consumption willingness (Deng et al, 2020). This study showed that the perceived threat of COVID-19 may related to a universal, non-target-specific aggressive tendency, provides a reference from first-hand data for subsequent studies.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 72%
“…The GAM explains the generation of aggression through how situation factors influence personal internal states such as cognitions, feelings, and arousal, which in turn affect aggressive or non-aggressive behavioral outcomes in appraisal and decision processes. During the COVID-19 pandemic in China, the perceived threat of COVID-19 caused a rapid increase in emotional issues (Gao et al, 2020), cognition stress (Xin et al, 2020), and arousal problems (Deng et al, 2020). As a result, people are higly likely to respond to rapidly increasing internal pressure by being aggressive.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Some evidence suggests that higher needs or preferences for sensation seeking input make it more difficult to withstand long-term input deprivation, although findings tend to be mixed. For example, sensation seeking was positively correlated with the boredom experienced during COVID-19 related lockdown, but life satisfaction during the pandemic was not associated with this trait (Deng, Wang, Xie, Chao, & Zhu, 2020). Moreover, higher boredom proneness was linked to more difficulty complying with social distancing during the lockdown (Boylan, Seli, Scholer, & Danckert, 2020;Wolff, Martarelli, Schüler, & Bieleke, 2020).…”
Section: Deprivationmentioning
confidence: 95%